Policy Formulation for Online Gambling Prevention in Campus Environments: A Case Study at Politeknik STIA LAN Bandung: Perumusan Kebijakan Pencegahan Perjudian Daring di Lingkungan Kampus: Studi Kasus di Politeknik STIA LAN Bandung - Noval, Muhammad Attala; Pradesa, Hafid Aditya; Abdullah, Sait; Nurliawati, Nita (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Digital betting has become a serious threat to student welfare, academic integrity, and institutional reputation in higher education. Specific Background In the studied vocational higher education environment, online gambling escalated from a private student problem into an institutional concern, as shown by illegal loan debt collection appearing in official communication channels and a USG Matrix score of 202, the highest among assessed social issues. Knowledge Gap Existing studies mainly discuss mental health, risk factors, and socioeconomic consequences, while internal policy formulation from a strategic management perspective in vocational higher education remains underexplored. Aims This study aims to formulate a strategic prevention framework using Kingdon’s Policy Window, Bryson’s Strategic Planning, and Rothman’s Community Intervention. Results Findings show that the convergence of problem severity, available institutional resources, and leadership commitment has opened a policy window for intervention. The study identifies punitive sanctions as counterproductive because they create fear and discourage early reporting. Novelty The proposed House of Integrity framework integrates Smart Monitoring, tiered educational sanctions, mandatory counseling, limited amnesty, and Peer Educator involvement through student organizations. Implications The framework offers a humane, measurable, and collaborative student protection system that supports early detection, rehabilitation, financial literacy, and institutional integrity. Highlights • The USG Matrix ranked digital betting as the highest priority social issue with a score of 202.• Punitive sanctions created fear, silence, and barriers to early reporting.• Peer Educators, counseling, and technical surveillance formed an integrated prevention framework. Keywords Smart Monitoring; Student Protection; Digital Betting; Policy Formulation; Higher Education